Kontribusi Pemerintah dalam Pengelolaan Zakat di Aceh (Kontestasi Penerapan Asas Lex Specialis dan Lex Generalis) - Armiadi Musa (Sharia and Law Faculty, 2017)
Aceh as the implementation of Islamic law that apply actually has a strong and comprehensive regulation in managing zakat management as one of the Islamic economic instruments that can be relied upon. No new provisions actually be said that the setting is global and thus requires the derivation of a general- derivation of other rules in accordance with the demands of today’s circumstances, especially if it is associated with some of the specifics that are given to Aceh in applying the principle of lex specialist in public law requirements within the framework of Islamic law. Terms and conditions of Zakat as Zakat PAD can reduce the payment of income tax payable is stipulated in Law 11/2006 (BAL) of the Government of Aceh and Aceh Qanun No. 10/2007 on the Baitul Mal is still being debated. This problem is triggered by the perception and understanding of the parties as to whether zakat diperlalukan as pure PAD managed according to Law No. 17 of 2003 on State Finance and Government Regulation (PP) No. 58/2005, of the Regional Financial Management or managed as a special revenue. Similarly, if the charity is paid muzakki in Aceh can decimate the income tax payable (tax-crediet) according BAL and Qanun above or must according to Law No. 7 of 1983 on Income Tax mentions zakat can only reduce the amount of taxable income (tax-deductable). This regulation conflicts must be resolved, among others, by mating / combination and fusion (matching) the existing rules so as not to be controversial, so the contribution of the Government of Aceh to the management of zakat is not marred by it.